The Concept of Spiritual Education in the Thought of Said Nursi - Asrori, Asrori; Huwaida, Jaziela (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2025)
Modern education today faces a crisis of values due to the dominance of secular and materialistic paradigms, which neglect the spiritual dimension of learners. In this context, the thoughts of Bediuzzaman Said Nursi offer a valuable conceptual alternative through a spiritual education framework that integrates religious sciences with modern knowledge. This study aims to explore in depth the concept of spiritual education in Said Nursi’s thought and its relevance to the development of contemporary Islamic educational curricula. The research employs a qualitative method with a library research approach, critically analyzing Nursi’s primary works—particularly the Risale-i Nur—as well as relevant secondary academic literature. The results of the study indicate that spiritual education according to Nursi is a process of shaping faith, character, and divine consciousness involving the intellect, heart, and soul. He proposes a holistic model of education that integrates medrese (religious schools), mektep (modern secular schools), and tekke (Sufi institutions), emphasizing key spiritual values such as acz (powerlessness), faqr (poverty), shafqat (compassion), and tafakkur (contemplation). This concept contributes significantly to the development of an Islamic curriculum that balances spiritual and intellectual aspects. The findings affirm that Said Nursi's thought is highly relevant to addressing contemporary educational challenges and can serve as a foundation for reconstructing a tawhid-based Islamic education curriculum grounded in spiritual values.